What does it mean to conduct participatory research with Indigenous peoples? A lexical review - Ann Dadich; Loretta Moore; Valsamma Eapen (BMC, 2019)
Abstract Background To better understand and promote public health, participatory research with Indigenous peoples represents recommended practice, worldwide. However, due to the different ways such research is referred to, described, and used, it is unclear what might (and might not) warrant the term when collaborating with Indigenous peoples. As such, this article expands conceptual understandings of participatory research with Indigenous peoples, across timelines and regions. Method Following a systematic search of 29 academic databases in April 2018, a lexical analysis of the methods sections was conducted, which were sourced from 161 publications across 107 journals. Results The active involvement of Indigenous peoples in research that is expressly participatory is limited across all project phases. This might be because the ways in which Indigenous peoples were involved throughout were not reported - however, it might also be because Indigenous peoples were not involved in all project phases. Furthermore, descriptions differ by study location and publication timeframe - notably, studies in the region of the Americas chiefly refer to pandemics, surveyors, and art; and those published in the last two decades have given primacy to artifacts of interest. Conclusions Findings from this corpus of data suggest participatory research with Indigenous peoples is not always described across different project phases; furthermore, it differs according to study location and publication timeframe. This offers considerable opportunity to further this important research area via alternative methodologies that award primacy to Indigenous expertise and agency.